Dielectric loss and phase transition of sodium potassium niobate ceramic investigated by impedance spectroscopy - Nobre, MAL; Lanfredi, S. (Elsevier B.V., 2003)
The dielectric permittivity of Na0.80K0.20NbO3 ceramic was investigated by impedance spectroscopy. The dielectric characterization was performed from room temperature to 800 degreesC, in the frequency range 5 Hz-13 MHz. The bulk permittivity was derived by the variation of the imaginary part of the impedance as a function of reciprocal angular frequency. The permittivity values as a function of temperature showed two maxima. The first maximum is very similar at 200degreesC and the second one positioned at around 400degreesC, which was associated to Curie's temperature. The evolution of the complex permittivity as a function of frequency and temperature was investigated. At low frequency dispersion was investigated in terms of dielectric loss. The Na0.80K0.20NbO3 showed a dissipation factor between 5 and 40 over a frequency range from 1 to 10(2) kHz. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: dielectric loss; phase transition; impedance spectroscopy